Comparison of several types of compact fluorescent lamp in terms of harmonic and illumination - Ahmad Ali Imran Mohd Ali, 1988-; Faridah Hussin, supervisor; Fakulti Kejuruteraan Elektrik (2011)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik)) - Universiti Teknologi Malaysia, 2011